Pogostemon cablin from North Konawe Targets MCF-7 Cells and Inflammatory Responses Through Protein Denaturation and Membrane Stabilization - Adryan Fristiohady; Jafriati Jafriati; Irvan Anwar; Rathapon Asasutjarit; La Ode Muhammad Julian Purnama; Lidya Agriningsih Haruna; Agung Wibawa Mahatva Yodha; Hariana Hariana; Mentarry Bafadal (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Pogostemon cablin (Patchouli), a medicinal plant traditionally used in Indonesia, is gaining scientific attention for its potential pharmacological activities. This study aimed to investigate the anti-inflammatory and anticancer effects of P. cablin ethanolic leaf extract specifically sourced from North Konawe, Southeast Sulawesi. To evaluate its anti-inflammatory activity, two in vitro models were used: the protein denaturation inhibition assay, simulating inflammatory protein response, and the human red blood cell (HRBC) membrane stabilization assay, which mimics lysosomal membrane stability in inflamed tissues. The extract showed significant, dose-dependent inhibition of protein denaturation, with an IC50 value of 62.98 µg/mL. In the HRBC assay, the extract demonstrated membrane stabilization activity with a maximum inhibition of 64.24% at the highest tested concentration (100 µg/mL). The cytotoxic potential was assessed using the MTT assay on MCF-7 hormone-responsive breast cancer cells. The extract exhibited potent anti-proliferative activity, with an IC50 value of 91.56 ± 1.31 µg/mL, indicating its effectiveness in inhibiting breast cancer cell growth. These findings highlight P. cablin from North Konawe as a promising natural source of anti-inflammatory and anticancer agents, with the potential to contribute to the development of plant-based therapeutics. However, this study is limited to in vitro analyses; further investigations are needed to isolate active compounds and confirm efficacy through in vivo and mechanistic studies.